First-line treatment with cadonilimab plus paclitaxel-platinum ± bevacizumab for persistent, recurrent, or metastatic cervical cancer: a retrospective real-world study - Wang, Xin; Wang, Chunsheng; Zong, Dan; Zhu, Biqing; He, Xia (Frontiers in Oncology, 2025)
BackgroundThe aim of this study was to assess the real-world effectiveness and safety of first-line treatment with cadonilimab plus paclitaxel-platinum ± bevacizumab for persistent, recurrent, or metastatic cervical cancer (p/r/m CC).MethodsIn this retrospective real-world study from Jiangsu Cancer Hospital (January 2021–February 2025), patients with p/r/m CC received first-line cadonilimab plus paclitaxel-platinum ± bevacizumab or paclitaxel-platinum ± bevacizumab. Co-primary endpoints were progression-free survival (PFS) and safety; overall survival (OS), objective response rate (ORR), and disease control rate (DCR) were secondary. Kaplan–Meier and log-rank methods were applied, with prognostic factors analyzed using Cox models.ResultsAmong 169 eligible patients (50 cadonilimab plus TP; 119 TP), median follow-up was 33.2 months [interquartile range (IQR): 12.2–35.2]. Cadonilimab addition significantly prolonged mPFS [20.2 vs. 12.2 months; hazard ratio (HR): 0.531, p = 0.019], with 12- and 24-month PFS rates of 65.83% and 48.62% versus 50.71% and 29.57%, respectively. ORR improved from 40.3% to 54.0%, while DCR remained high in both cohorts (92.0% vs. 90.8%). mOS was not reached in the cadonilimab plus TP group and was 37.5 months with TP alone. Cadonilimab increased low-grade immune-related or gastrointestinal adverse events, with the most common being rash or itching (38.0%), pyrexia (32.0%), constipation (58.0%), and diarrhea (50.0%). However, events in grades 3–5 were infrequent. Subgroup analyses showed a generally consistent PFS benefit with cadonilimab across most predefined patient subsets.ConclusionsIn real-world clinical settings, cadonilimab plus TP ± bevacizumab provides a durable PFS benefit with acceptable safety and supports first−line use for p/r/m CC; additional follow-up is essential to determine its impact on OS.